On the Civiliarchic Dimension of Democracy - Aleksanyan, Ashot (YSU Journal of International Affairs, 2019)
The article examines the issues of the civiliarchic dimension of democracy, identifies the features of the civiliological approach, as well as the importance of regime and power resources for the rational design of the dialogue and partnership between the state and civil society organizations. Based on the concept of modern democracy, important factors of human rights and freedoms, individualism, the rule of law, constitutionalism and liberalism are analyzed, a new definition of the concept of “civiliarchic democracy” is given, its specific features and values are explained. It is argued that the effectiveness, constructiveness and civilicentricity of democracy as the power of the people and as a political regime is realizable based on a civiliarchical mechanism and institutions.
Keywords: democracy; demarchy; civilicracy; civiliarchy; dialogue; partnership; development; human rights and freedoms; dichotomy; citizen-centric; civilicentric